2015
DOI: 10.3233/bmr-140482
|View full text |Cite
|
Sign up to set email alerts
|

Upper trapezius relaxation induced by tens and interferential current in computer users with chronic nonspecific neck discomfort: An electromyographic analysis

Abstract: IFC induced the upper trapezius relaxation after 3 sessions in females with neck discomfort, but the TENS application did not change the muscular tension. However, these results should be carefully interpreted due to the lack of differences between groups. A significant pain decrease was found in the subjects of both groups, however, only the IFC application presented a clinically important improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
1
25
1
Order By: Relevance
“…Both are validated and well-established in the literature 10,13,15 . Despite the reports that the electrical stimulation positively affects the treatment of individuals with neck pain, such as TENS 12,16,17 and the Interferential 11 , in this study, the variables related to pain and disability did not present differences in relation to the baseline values or intergroup. Corrêa et al 18 observed in individuals with chronic low back pain that the interferential current, of 1 and 4kHz (AMF of 100Hz, for 30 minutes, 3 days a week for 4 weeks), produced significant reduction in pain intensity.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Both are validated and well-established in the literature 10,13,15 . Despite the reports that the electrical stimulation positively affects the treatment of individuals with neck pain, such as TENS 12,16,17 and the Interferential 11 , in this study, the variables related to pain and disability did not present differences in relation to the baseline values or intergroup. Corrêa et al 18 observed in individuals with chronic low back pain that the interferential current, of 1 and 4kHz (AMF of 100Hz, for 30 minutes, 3 days a week for 4 weeks), produced significant reduction in pain intensity.…”
Section: Discussioncontrasting
confidence: 96%
“…The increased use medium frequency currents in rehab follows the theory that they are more comfortable and more effective than of low-frequency currents since the first has a lower impedance on the skin, being able to stimulate deeper tissues, although reports point out varied antinociceptive effects between currents [11][12][13] . There is a need for new research with electrostimulation in the treatment of spinal pain 14 .…”
Section: Discussionmentioning
confidence: 94%
“…Also, Acedo et al [22] compared muscle relaxation of the upper trapezius induced by the application of transcutaneous electric nerve stimulation and iFT in females with chronic nonspecific neck discomfort to reveal if a decrease in muscular activity could be observed at sensorial level stimulation in medium-frequency current, using current intensity (mA) only in the sensory threshold. The authors found that iFT induced upper trapezius relaxation after 3 sessions in females with neck discomfort, but applying transcutaneous electric nerve stimulation did not change the muscular tension.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared the RMS values after IT with the RMS values before IT in order to examine changes in muscle tension. This method was used in a study by Acedo et al 11 ) , and like that study, we were able to obtain results showing changes in muscle tension. Moreover, we obtained another interesting result.…”
Section: Discussionmentioning
confidence: 62%